ANALISIS “TOXIC PARENTS” DALAM KELUARGA TERHADAP PERILAKU EMOSIONAL ANAK USIA 5-6 TAHUN DI DESA BAH TOBU KECAMATAN DOLOK BATU NANGGAR KABUPATEN SIMALUNGUN - Dinda Rahmayani; Kamtini (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the emotional behavior of children aged 5-6 years who come from toxic parents families in Bah Tobu Village, Dolok Batu Nanggar District, Simalungun Regency. This study is a qualitative research type. The subjects of this study were 5 parents and 5 children aged 5-6 years in Bah Tobu Village. The researchers collected data through observation and interviews. For data analysis in this study, three methods were employed: data reduction, data presentation, and drawing conclusions. The validity of the data used in this study was triangulation. Based on the results of the study, of the five parents who were sampled, two parents had the types of Pageant Parents, Dismissive Parents, and Contemptous Parents. One had the types of Pageant Parents and Contemptous Parents, another had the types of Dismissive Parents and Contemptous Parents and the other one only had the type of Contemptous Parents. These three types of Toxic Parents have an impact on children's emotional behavior. So it can be related to the treatment of toxic Parents can be related to the emotional behavior of children aged 5-6 years in Bah Tobu Village, Dolok Batu Nanggar District, Simalungun Regency.